2010
DOI: 10.1080/00397910903029875
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synthesis of 3-Alkoxyacrylic Acid Esters Under Neat Conditions

Abstract: Triethylamine or Ph 3 P (0.05 eq.) was found to catalyze the addition of alcohols to alkyl propiolates. The reaction occurred much more rapidly without solvent than in solvent. The E/Z ratio was relative to the reaction temperature. Water was found to inhibit the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While the oxa‐Michael addition of an alcohol to propiolate has been reported, to the best of our knowledge, it has not been applied to the synthesis of CA (PEG) n ‐type molecules. To our delight, treatment of compound 11 (1.0 to 1.5 Eq) with 1 Eq of benzyl propiolate ( 18 ) in the presence of N ‐methylmorpholine in CH 2 Cl 2 at room temperature gave adduct 21 smoothly in 89% isolated yield (Scheme ).Dibenzyl 3,3'‐oxy‐diacrylate, formed due to the presence of trace amount of water, was also isolated in 4% yield from the reaction and it was easily removed chromatographically .…”
Section: Resultsmentioning
confidence: 99%
“…While the oxa‐Michael addition of an alcohol to propiolate has been reported, to the best of our knowledge, it has not been applied to the synthesis of CA (PEG) n ‐type molecules. To our delight, treatment of compound 11 (1.0 to 1.5 Eq) with 1 Eq of benzyl propiolate ( 18 ) in the presence of N ‐methylmorpholine in CH 2 Cl 2 at room temperature gave adduct 21 smoothly in 89% isolated yield (Scheme ).Dibenzyl 3,3'‐oxy‐diacrylate, formed due to the presence of trace amount of water, was also isolated in 4% yield from the reaction and it was easily removed chromatographically .…”
Section: Resultsmentioning
confidence: 99%
“…On a 100 g scale, dibenzylamine was added to neat methyl (2 R )-glycidate 2 at 70 °C, affording a quantitative yield of crude methyl (2 R )-3-(dibenzylamino)-2-hydroxypropanoate 3 . Conjugate addition of 3 to methyl propiolate gave a 93:7 mixture of the E and Z isomers of 4 in 98% overall yield and subsequently, hydrogenation using palladium hydroxide as a catalyst, afforded methyl (2 R )-3-amino-2-(3-methoxy-3-oxopropoxy)propanoate 5 (82% w/w, 87% effective yield) . Upon neat storage we found that the amino diester 5 was unstable and slowly polymerized, but in a solution of, e.g., dioxane or methanol it was stable for weeks at +5 °C.…”
Section: Results and Discussionmentioning
confidence: 99%